Heart rate variability behavior in athletes after a sports concussion: A systematic review - Flores, G.; Monteiro, D.; Silva, F.; Duarte-Mendes, P. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Objective This systematic review aims to investigate the adaptations of the autonomic nervous system (ANS) after a concussion by measuring HRV in athletes over the age of 16 after injury.